The consequences of child-parent violence reflected in a life story - Trujillo Vargas, José Jesús; Sahagún Navarro, Marta; Cárdenas Rodríguez, Rocío; Ramírez Giraldo, Andrés Fernando (Cuadernos de Trabajo Social, 2016)
A process of social transformation allied with ongoing changes to the family has made possible the existence of a relatively little-known phenomenon: that of child-parent violence, which is raised as one of the most commonly experienced forms of violence in the family environment. Based on the study of this phenomenon, in our research we have used the qualitative technique of a life story, making use of a field diary in which we have taken notes on our daily work in the therapeutic context, for the purposes of mitigating the effects of such a process. The following research objectives were set: establishing the connection existing between family education style and the use of violence by the minor; and evaluating the extent to which family therapy mitigates the use of violence by the minor. The family education model, together with other dimensions, results in situations of child-parent violence occurring repeatedly, with continuing negative reinforcement from both parties in order to maintain a recurrent cycle of conduct, from which it is difficult to «escape» other than through a process of ongoing psychological therapy.